2005
DOI: 10.1177/0363546504273047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatigue on Knee Kinetics and Kinematics in Stop-Jump Tasks

Abstract: Fatigued recreational athletes demonstrate altered motor control strategies, which may increase anterior tibial shear force, strain on the anterior cruciate ligament, and risk of injury for both female and male subjects. CLINIC RELEVANCE: Fatigued athletes may have an increased risk of noncontact anterior cruciate ligament injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
332
8
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(373 citation statements)
references
References 34 publications
24
332
8
9
Order By: Relevance
“…Sagittal-plane knee mechanics were altered with fatigue; specifically, a decrease in knee flexion was seen at peak vertical ground reaction force, peak posterior ground reaction force, and peak knee flexion. Researchers who did not completely use a SLO-FP or FAST-FP but induced lower extremity fatigue found similar results for these kinematic variablesy, 12,20 An interesting result to note is the lack of difference between fatigue protocols (SLO-FP and FAST-FP). Most prefatigue to postfatigue changes were observed regardless of the fatigue protocol used, with minimal differences noted between the 2 protocols.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Sagittal-plane knee mechanics were altered with fatigue; specifically, a decrease in knee flexion was seen at peak vertical ground reaction force, peak posterior ground reaction force, and peak knee flexion. Researchers who did not completely use a SLO-FP or FAST-FP but induced lower extremity fatigue found similar results for these kinematic variablesy, 12,20 An interesting result to note is the lack of difference between fatigue protocols (SLO-FP and FAST-FP). Most prefatigue to postfatigue changes were observed regardless of the fatigue protocol used, with minimal differences noted between the 2 protocols.…”
mentioning
confidence: 93%
“…ll ,12,20Chappell et al 12 found a decrease in knee flexion angle at peak proximal tibial anterior shear force in a stop-jump 12 We analyzed knee flexion at peak posterior ground reaction force and peak vertical ground reaction force, both of which have been shown to be correlated with peak proximal tibial anterior shear force,37 and found a decrease of 6.9% (prefatigue=-38.4°, postfatigue=-35.8°) and 7.4% (prefatigue= -38.8°, postfatigue =-35.9°), respectively. The percentage change for our study was smaller than the change reported by Chappell et al 12 The smaller decrease in knee flexion angle in our study could be a result of the increased level of conditioning and athletic ability present in our participants. However, the reduced knee flexion angle at peak posterior ground reaction force still might be increasing the load on the ACL, thereby increasing its likelihood of rupture.…”
mentioning
confidence: 99%
“…Traditionally, knee loading has been quantified using an inverse dynamics approach to estimate the resultant forces at the tibiofemoral joint. 27 However, this approach does not consider muscle forces and their contributions to joint loading. 28 While several advanced methods (i.e., inverse dynamics optimization and forward dynamics) have been proposed to estimate individual muscle forces, 29,30 a common limitation of these approaches is the inability of predicting antagonist muscle forces because of the lack of information regarding muscle co-contraction.…”
mentioning
confidence: 99%
“…However, little scientific study has studied other functional abilities. The vertical jump, for example, is an important functional activity that is commonly applied in training and rehabilitation 11 . Mechanical loading during childhood, based on jumping activities, for example, plays a critical role in normal growth and development of the skeleton 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In preparation for the CVJ that demands high angular amplitude 11 , CF children had a limitation in ankle movement that can be caused by the residual stiffness within the foot that is characteristic of the pathology's evolution. This restriction on movement was used by Davies, Kiefer, Zernicke 2 to explain, in gait analysis, reduced plantarflexion during push-off for CF groups.…”
Section: Discussionmentioning
confidence: 99%